Pendidikan Kebangsaan Perspektif Kh. Wahab Chasbullah - Atiqah Qudsiyah; Hanifuddin Mahadun; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2023)
Islamic education has an integral role in shaping the spirit of patriotism in Indonesia, especially through the contribution of KH. Abdul Wahab chasbullah in building national education that integrates Islamic values with the spirit of nationalism. In his efforts to pioneer the foundation of education, KH. Abdul Wahab Chasbullah combines Islamic values with national spirit as the main foundation, reflecting the importance of unity between the two. This research wants to know the concept of national education according to KH. Abdul Wahab chasbullah specifically and how KH struggled. Wahab Chasbullah in building national education. This research analyzes the concept of education held by KH. Abdul Wahab Chasbullah through library research methods and a philosophical approach using primary data sources such as directly related books and articles. The results of this research show that KH. Wahab Chasbullah, a major figure from NU, played a key role in fostering dialogue between nationalism and religiosity and fighting for Islamic education that was balanced between logic and feeling, by emphasizing the importance of tolerance, liberation, patriotism, humanism, pluralism and unity as fundamental values for Indonesian society.